PENGARUH LINGKUNGAN SEKOLAH TERHADAP HASIL BELAJAR TEKNOLOGI DASAR OTOMOTIF SISWA KELAS X TSM DI SMK KRISTEN GETSEMANI MANADO - Walid Saleh; Parsaoran Tamba; Denny Maukar (GEARBOX: Jurnal Pendidikan Teknik Mesin, 2022)
This study aims to determine whether there is an influence of the school environment on the results of learning basic automotive technology for students of class X at Getsemani Christian Vocational High School, Manado. This research is quantitative descriptive. Because everything that has been researched has been done empirically. The population in this study amounted to 30 students. And the sample in this study was taken from the total population of 30 students. Data collection techniques using documentation studies, namely by taking the results achieved by students, on the results of the final semester exams and questionnaires or questionnaires. The data analysis technique used the SPSS version 22 program, namely to determine the relationship between the variables studied. The results of this study indicate that there is a relationship between the school environment and learning outcomes with the equation Y=27.948+ 0.712% and from the test results it is also found that there is a significant effect between the school environment on learning outcomes, namely (r2) = 0.899 or 94.8%.